Social Filter Theory—A Sleeping Beauty of Regional Innovation Theories - Ren, Jianhui; Lai, Linlin; Pei, Binjie; Zhan, Wenyu (Regional Science and Environmental Economics, 2024)
As a branch of regional innovation theories, social filter theory fundamentally reveals the reasons behind the geography of innovation in different countries and regions. However, compared with other regional innovation theories, social filter theory has remained largely ignored and has not been fully developed. To enrich and develop social filter theory, this article systematically traces its origins and comments on four aspects: the concept of social filters, the construction and measurement of social filter indicators, the mechanisms, and empirical research on how social filters affect regional innovation and the transformation of innovation. Until recently, regional innovation theories primarily focused on superficially describing the phenomenon of innovation, but they paid little attention to the local social filter conditions necessary for innovation generation and transformation, which are prerequisites for constructing a mature innovation system. Therefore, further efforts are needed to address the current knowledge gap based on the recommended directions in this article.